The challenge of using date branch waste as a peat substitute in container nursery production of lettuce (Lactuca sativa L.) - Najla Dhen; Safa ben Abed; Amin Zouba; Faouzi Haouala; Bouthaina AlMohandes Dridi (International Journal of Recycling of Organic Waste in Agriculture)
Abstract Purpose Peat-based substrates constitute the preferred media in conventional and organic nursery production. Nevertheless, in recent years, there has been a growing interest in environmental impacts associated with peat extraction that has increased with the demand of these non-renewable substrates. The re-use of organic wastes as substrate seems to be good solution to substitute commercial peat. This study evaluates date-palm peat (wastes of date-palm branches base locally known as “Kornef”) as an alternative nursery substrate. Methods The research was conducted in a completely block randomized design with a linear substitution (0, 25, 50, 75 and 100%) of peat with date-palm waste peat for transplant production of lettuce (Lactuca sativa L.). Different physicochemical parameters (porosity, bulk density, pH, and CEC) of cultivation substrates were measured. The growth parameters (leaves number, leaves area, length, chlorophyll values, fresh and dry weight of seedlings) were evaluated at the end of growth period (when the seedling reached the commercial transplanting size). Results The results showed that date-palm waste peat is an appropriate media for nursery production, showing similar properties with commercial peat and best plant response with 25 and 50% substitution. Conclusions In view of low cost, availability and large area of date-palm cultivation in Tunisia and over the world, it seems that peat can be replaced with substrate of date-palm wastes in the horticulture sector.